Editorial preface - La Rocca, Rosa Anna (TeMA - Journal of Land Use, Mobility and Environment, 2024)
This Special Issue of TeMA - Journal of Land Use, Mobility and Environment proposes to delve into the concept of transition applied to urban and territorial systems with the aim of verifying the state of the art in scientific as well as in technical sector, also considering the effects of Covid-19pandemic crisis (Angiello, 2021). What is urgent is the need to change both social behaviors and the use of primary resources (water, energy and soil) which is claimed by technicians and scholars as the only solution to face environmental challenges affecting nowadays cities. These challenges and the linked risks are so relevant that an in-depth change in the operative actions as well as in the theoretical approaches has become mandatory, in order to avoid negative and disruptive effects. with this Special Issue we intended to draw the attention of technicians and scholars to the theme of urban transition which from many quarters seems to prefer the "ecological dimension" to pursue sustainability objectives. The eleven contributions received, while maintaining the underlying theme of the main theme, propose differentiated perspectives of sustainable transition which can be divided into three groups: Methodologies and cognitive tools for urban transition Urban policies and driver elements of the urban transition Possible projects and applications for urban transition The contributions of the first group propose analysis methodologies oriented to the knowledge of the changes affecting cities, they try to identify adaptation solutions suitable for these changes. In particular, the aspects relating to the vulnerability of cities to the effects of climate change, the need to develop adequate tools to support informed decision-making processes, to define territorial planning tools capable of integrating the transition through the construction of a system of clear rules. The contributions of the second group focus on the analysis of the effects deriving from climate change, highlighting the urgency of integrating adaptation and mitigation actions within the process of defining land use policies at different scales. Aspects relating to the framework of European "green" policies are explored in depth, as well as the need for integration between urban planning and environmental assessment tools, and the search for appropriate methods and tools to improve the adaptation and resilience capacity of urban systems to the need to define approaches based on a holistic and systemic vision for the knowledge of urban phenomena at different scales. The contributions of the third group allow for the building of a first cognitive framework related to research projects and/or urban planning practices aimed at identifying interventions to improve the conditions of urban sustainability, with particular attention to "fragile" territories (lagoon areas, internal areas, coastal areas). Aspects related to the feasibility of creating zero energy emission urban districts as well as the definition of actions for the protection of urban ecosystems are always explored in depth with a view to tracing practicable and sustainable trajectories of change.